Trend in overweight and obesity among women of reproductive age in Uganda: 1995-2016 - S. Yaya; B. Ghose (Wiley, 2019)
Summary Countries in Sub‐Saharan Africa (SSA) are experiencing rising burdens of overweight/obesity and associated non‐communicable diseases. As in other developing regions, this epidemiological transition in African countries is believed to be resulting from changes in dietary, sociodemographic structure and lifestyle factors. To date, not much is known about the prevalence and sociodemographic patterns of overweight/obesity in Uganda, especially among women of reproductive age. Therefore, this study aimed to address this research gap by using nationally representative data on women of this age group in Uganda. Methods This study involved analysis of cross‐sectional data on 19,395 women aged between 15 and 49 years from Uganda Demographic and Health Survey for the years 1995-2016. Overweight/obesity was measured using body mass index as per World Health Organization guidelines, and logistic regression methods were used to identify the sociodemographic predictors. Results There has a been significant rise in the prevalence of overweight (9.77% in 1995 vs. 16.21% in 2016) and obesity (1.99% in 1995 vs. 6.21% in 2016) since the first survey in 1995, with the most noticeable increase occurring in the central region that accounted for a combined prevalence of 17.22% in 1995 compared with 37. 21% in 2016. Multivariate analysis showed an increased likelihood of having overweight/obesity among women who live in the urban areas, have primary and above primary education, from non‐poor households and users of radio and TV. Conclusion During the last two decades, there has been a slow but steady rise in the prevalence of overweight and obesity among women of reproductive age in Uganda. The present findings highlight the need for an enhanced attention on growing overweight/obesity within the broader goal improving maternal and child health in the country.